Pricing-to-market as an Example of Price Differentiation in European Markets - Misztal, Piotr (Comparative Economic Research. Central and Eastern Europe, 2025)
The aim of the research is to assess the degree of the pricing-to-market (PTM) strategy used in selected European countries, focusing on selected groups of consumer goods. The study uses a literature review in the field of macroeconomics and international finance, as well as statistical and econometric methods. The results of the research confirmed the occurrence of PTM in selected European countries, although the level differed significantly between countries. There is a positive correlation between the level of PTM and a country’s level of economic development. The highest PTM levels occurred for homogeneous rather than heterogeneous consumer goods. Our findings are extremely important, especially from the perspective of international companies. Understanding the elasticity of demand in different markets helps businesses set prices that maximize revenue. Setting prices too low or too high can affect how a brand is perceived in the market. By employing a PTM strategy, businesses can balance profitability with market competitiveness. To date, no comprehensive research has been conducted into PTM strategies in European markets. Therefore, this research fills the gap in this area, constituting a significant contribution to empirical research in the field of pricing strategies.